The Role of Student Self-Assessment in IAKN Ambon: Promoting Need-Supportive Christian Educational Practices - Novita Loma Sahertian; Benjamin Metekohy; Noni Matital; Tobias Dominggus Sohilait (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2025)
Promoting sustained academic engagement among university students remains a persistent and complex challenge. Alarmingly, many higher education institutions continue to report low levels of student involvement, particularly in areas requiring integration competence and awareness of equality issues. In response to this phenomenon, the present study explores student self-assessment (SSA) as a pedagogical instrument to strengthen the connection between need-supportive teaching and desired learning outcomes. Specifically, the study proposes the incorporation of SSA into routine teaching evaluation practices as a means to enhance student understanding, foster autonomy, and promote inclusive learning environments. The primary objective of this study research was to examine the impact of SSA on students’ academic performance within the context of a